(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the frequency, age, gender and laterality related distribution of retinoblastoma. Study design: Cross sectional study. Place and Duration of study: This study was conducted at the Department of pathology BMSI, JPMC Karachi from 1st Jan 2009 to 31st Dec 2013. Materials and Methods: A total of 80 cases of retinoblastoma were received in the department of Pathology, BMSI, JPMC, Karachi during the period of 1st January 2009 to 31st December 2013. The cases were reviewed and morphological diagnosis done on H&E. Information regarding laterality of lesion, age and sex were recorded from archives. The data analyzed by using SPSS version 22. Results: Frequency of retinoblastoma was 2.93%. Right sided lesions were 46.25% & 45% were Left sided, with a M: F ratio of 1:1. The mean age of retinoblastoma patients was 3.64 years. It was relatively more common in 3 to 4 years (53.75%) of age group compared to other age groups. Conclusion: Frequency of retinoblastoma was 2.93%, with almost equal i-e 46.25% Right, 45% Left sided origins. The M: F ratio was 1:1 while more common age group was 3 to 4 years.